Trehalase plays a role in macrophage colonization and virulence of Burkholderia pseudomallei in insect and mammalian hosts. Issue 1 (2nd January 2017) - Vanaporn, Muthita; Sarkar-Tyson, Mitali; Kovacs-Simon, Andrea; Ireland, Philip M.; Pumirat, Pornpan; Korbsrisate, Sunee; Titball, Richard W.; Butt, Aaron
ABSTRACT: Trehalose is a disaccharide formed from two glucose molecules. This sugar molecule can be isolated from a range of organisms including bacteria, fungi, plants and invertebrates. Trehalose has a variety of functions including a role as an energy storage molecule, a structural component of glycolipids and plays a role in the virulence of some microorganisms. There are many metabolic pathways that control the biosynthesis and degradation of trehalose in different organisms. The enzyme trehalase forms part of a pathway that converts trehalose into glucose. In this study we set out to investigate whether trehalase plays a role in both stress adaptation and virulence of Burkholderia pseudomallei . We show that a trehalase deletion mutant ( treA ) had increased tolerance to thermal stress and produced less biofilm than the wild type B. pseudomallei K96243 strain. We also show that the Δ treA mutant has reduced ability to survive in macrophages and that it is attenuated in both Galleria mellonella (wax moth larvae) and a mouse infection model. This is the first report that trehalase is important for bacterial virulence.